2020
DOI: 10.1002/jcb.29680
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of adipocyte differentiation by low‐intensity pulsed ultrasound via inhibition of insulin signaling and promotion of CCN family protein 2

Abstract: Adipocyte differentiation is regulated by several transcription factors such as the CCAAT/enhancer-binding proteins (C/EBPs) and peroxisome proliferatoractivated receptor-γ (PPARγ). Here, we demonstrate that low-intensity pulsed ultrasound (LIPUS) suppressed differentiation into mature adipocytes via multiple signaling pathways. When C3H10T1/2, a mesenchymal stem cell line, was treated with LIPUS (3.0 MHz, 60 mW/cm 2) for 20 minutes once a day for 4 days during adipogenesis, and both the number of lipid drople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Collectively, cortical actin organization via Rac1 activation promotes the translocation of SOX9 into the nucleus; and as a result, CCN2 expression is up-regulated. On the other hand, although differentiating adipocytes undergo cortical actin organization as well, CCN2 expression is remarkably down-regulated in them [65] . Additionally, LIPUS treatment decreases cortical actin and increases CCN2 expression, repressing their adipogenic differentiation [65] .…”
Section: Role Of Ccn2 As a Pivotal Regulator Of Mechanical Stress Resmentioning
confidence: 97%
See 2 more Smart Citations
“…Collectively, cortical actin organization via Rac1 activation promotes the translocation of SOX9 into the nucleus; and as a result, CCN2 expression is up-regulated. On the other hand, although differentiating adipocytes undergo cortical actin organization as well, CCN2 expression is remarkably down-regulated in them [65] . Additionally, LIPUS treatment decreases cortical actin and increases CCN2 expression, repressing their adipogenic differentiation [65] .…”
Section: Role Of Ccn2 As a Pivotal Regulator Of Mechanical Stress Resmentioning
confidence: 97%
“…On the other hand, although differentiating adipocytes undergo cortical actin organization as well, CCN2 expression is remarkably down-regulated in them [65] . Additionally, LIPUS treatment decreases cortical actin and increases CCN2 expression, repressing their adipogenic differentiation [65] . As it is reported that peroxisome proliferator-activated receptor (PPAR)γ, which is an essential transcription factor for adipogenesis, inhibits CCN2 expression [76] , these findings suggest that the PPARγ decreased by LIPUS treatment increases CCN2 expression in adipocytes.…”
Section: Role Of Ccn2 As a Pivotal Regulator Of Mechanical Stress Resmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, chronic inflammation has been demonstrated to be a key player in the development of diabetes and its complications (116)(117)(118). The cells involved in these diseases, including adipocytes, have been shown to respond under the stimuli of LIPUS (119,120). It is possible that the anti-inflammatory effects of LIPUS could play an important role in the treatment of diabetes, and future research should be conducted.…”
Section: Prospect and Limitationmentioning
confidence: 99%
“…To isolate total RNA from HCS-2/8 cells, RCS cells, and xiphoid process-derived chondrocytes, we used ISOGEN reagent (Nippon Gene, Tokyo, Japan). First-strand cDNA was synthesized from 1 µg of total RNA by a primerScript TM RT reagent kit (Takara Shuzo, Tokyo, Japan), and subsequent quantitative PCR analysis was performed with the SYBR ® Green Real-time PCR Master Mix (Toyobo, Tokyo, Japan) using the StepOne Plus real-time PCR machine (Applied Biosystems, Carlsbad, CA, USA) as described previously [32]. The specific primer sequences and the GenBank accession numbers of the target genes are shown in Table 2.…”
Section: Quantitative Reverse Transcription (Rt)-pcr Analysismentioning
confidence: 99%